Independence and mobility in later life - Schwanen, T; Banister, D; Bowling, A (Elsevier, 2012)
This paper explores independence in later life and its relations with mobility, or embodied movements through physical space on the basis of a review of a range of academic literature and in-depth interviews with community-dwelling adults aged 70 and more in the UK. We suggest that independence is a complex and fuzzy notion that is best thought of as a qualitative multiplicity and as an unstable achievement fabricated out of dependencies on bodies, technologies, infrastructures, social networks and other elements. Yet we also find that the study participants understand independent mobility as avoiding lifts provided by next of kin, friends or others for getting around. This is tied to the enactment of particular forms of embodiment and ageist subject positions for older people and implies that older adults are inadvertently complicit in the perpetuation of the connotations of dependency in later life with passivity, burden and undesirability. To counteract these tendencies, we end this paper by elaborating more inclusive and broader conceptualisations of dependence, independence and independent mobility in later life.